Present state of research on ticks (Ixodoidea) in the Czech Republic - Dusbábek, F (Wiadomosci parazytologiczne, 1995)
Tick research in the Czech Republic started developing rapidly after World War II and was directed to the faunistics and taxonomy, biology, ecology and behaviour, physiology and genetics, disease transmission, host-parasite relationships and control. Altogether 15 tick species were reported from the territory of the Czech Republic. Most studies in biology, ecology and virus transmission were dedicated to Ixodes ricinus, but biology and ecology of Dermacentor reticulatus, I. laguri and I. hexagonus were also studied. Many studies were done on argasid ticks, mostly on pheromonal communication of Argas persicus and immunology of feeding of A. polonicus. Population variability of both these species was also studied. The present research on ticks is mostly directed to study of interaction among hosts, ticks and pathogens on the humoral, cellular and molecular level.
Keywords: Ticks; druhová specificita; Chickens; Arachnid Vectors; Adaptation, Physiological; Host-Parasite Interactions; entomologie; myši inbrední BALB C; zvířata; myši; arachnida jako vektory; Mice; kur domácí; Columbidae; klíšťata; Entomology; kontrola klíšťat; Czech Republic; Species Specificity; fyziologická adaptace; Animals; ekologie; Tick Control; Česká republika; interakce hostitele a parazita; Mice, Inbred BALB C; Ecology